Solubilization and Partial Purification of the Adenosine Triphosphatase from a Corn Root Plasma Membrane Fraction - Dupont, Frances M. (1980)
The K(+)-stimulated ATPase was partially purified from a plasma membrane fraction from corn roots (WF9 × Mo 17) by solubilization with 30 millimolar octyl-β-d-glucopyranoside followed by precipitation with dilute ammonium sulfate. The specific activity of the enzyme was increased about five times by this procedure. The molecular weight of the detergent-extracted ATPase complex was estimated to be at least 500,000 daltons by chromatography on a Bio-Gel A-5m column. Negative staining electron microscopy indicated that the detergent-extracted material consisted of amorphous particles, while the ammonium sulfate precipitate was composed of uniform vesicles with an average diameter of 100 nanometers. The protein composition of the ammonium sulfate precipitate was significantly different from that of the plasma membrane fraction when compared by sodium dodecyl sulfate gel electrophoresis. The characteristics of the partially purified ATPase resembled those of the plasma membrane associated enzyme. The ATPase required Mg(2+), was further stimulated by K(+), was almost completely inhibited by 0.1 millimolar diethylstilbestrol, and was not affected by 5.0 micrograms per milliliter oligomycin. Although the detergents sodium cholate, deoxycholate, Triton X-100 and Lubrol WX also solubilized some membrane protein, none solubilized the K(+)-stimulated ATPase activity. Low concentrations of each detergent, including octyl-β-d-glucopyranoside, activated the ATPase and higher concentrations inactivated the enzyme. These results suggest that the plasma membrane ATPase is a large, integral membrane protein or protein complex that requires lipids to maintain its activity.